Stability analysis for malt quality parameters in barley (Hordeum vulgare L.) - Kavitha, Govind; Singh, Sarvjeet; Dhindsa, Gurnam Singh; Sharma, Achla; Singh, Johar (Journal of Cereal Research, 2012)
Twenty malt barley genotypes comprising 7 commercial cultivars and 13 elite genotypes were evaluated for malt quality parameters in 8 environments during winters of 2005-06 and 2006-07. The environments were created by agronomic manipulation of dates of sowing and levels of nitrogen to determine the genotype x environment interaction and stability of genotypes for test weight, grain plumpness, husk content, grain protein content, Î±-amylase activity and diastatic power. Genotypes x environment interactions were significant for all the characters under study. Most of the genotypes did not satisfy the three criteria of stability model. These results indicated that the effect of non-linear component was more than the linear component. Thus, suggesting the requirement of specific genotype for a specific environment. According to stability parameters BK203 and VJM 514 for test weight; BK 201, BL 16 and PL 796 for plump grains; BL 61 for husk content; K 551(c), VJM 540 and DWRUB 52(c) for grain protein content; BL 71 for Î±-amylase activity; and VJM 201(c) and BL 48 for diastatic power were found to be relatively stable over the environments.